Kan die GKSA na 150 jaar beskou word as ’n stagnante kerkgemeenskap? Ekumenies beoordeel - C. J. Smit (In die Skriflig, 2009)
Should the RCSA after a period of 150 years be considered as a stagnated church community? Evaluated from the point of view of ecumenicism The question is whether the Reformed Churches in South Africa (RCSA) should be considered as an isolated and thus a stagnated church community. To answer this question the de- velopment of ecumenicism in the RCSA should be traced. This could only be done after an examination of the Scriptural and historical meaning of the term “ecumenicism”. From the acts of the synods of the RCSA it is very clear that during the three phases of half a century each in the existence of the RCSA, from 1859 onwards, a very high premium was put on ecume- nical relations. The goal of these ecumenical relations was always pointed out as church unity.